APPLYING TEXTUAL METAFUNCTION IN EFL WRITING: AN APPROACH TO TEACH WRITING - Setyo Prasiyanto Cahyono (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2012)
The Systemic Functional Linguistics (SFL) approach, specifically the textual metafunction, has been tried to be applied in teaching writing to English as a Foreign Language. SFL is chosen as an alternative application in language teaching since linguistics is the study of language that seeks how language works. Traditionally textual metafunction has often been neglected in language teaching, where sentences have been created, manipulated, and assessed in isolation. In EFL writing classroom, we find that learners often write paragraphs that consist of sentences which do not seem to connect together into cohesive devices. Thinking of this, I started to seek an alternative approach to help the students improve their writings, that is how to develop ideas so that the texts the students produce will run â€œsmoothlyâ€ and â€œhang togetherâ€ logically. It means that the sentences in their writings are well organized and developed coherently. Besides, the ideas will not jump from one idea to other ideas.Â This paper attempts to depict how to apply textual metafunction in EFL writing and how thematic patterns, which involves the relationship between clauses based on the information contained in themes and rhemes, can achieve cohesion in EFL learnersâ€™ text. It is assumed that the thematic patterns specify its usefulness as a discourse tool for adding students in writing their paragraph into cohesive text. The result shows that thematic patterns is one way of achieving cohesion in text since it involves connecting sentences together in a way which moves the text from the Given to the New. In short, the thematic pattern of texts is needed to analyze their own text to check for thematic flow in order to get a good cohesive text. Keyword: Cohesive text, EFL, SFL, Thematic Patterns